2011
DOI: 10.1111/j.1476-5381.2011.01340.x
|View full text |Cite
|
Sign up to set email alerts
|

TS-071 is a novel, potent and selective renal sodium-glucose cotransporter 2 (SGLT2) inhibitor with anti-hyperglycaemic activity

Abstract: BACKGROUND AND PURPOSEThe renal sodium-glucose cotransporter 2 (SGLT2) plays an important role in the reuptake of filtered glucose in the proximal tubule and therefore may be an attractive target for the treatment of diabetes mellitus. This study characterizes the pharmacological profile of TS-071 ((1S)-1,5-anhydro-1-[5-(4-ethoxybenzyl)-2-methoxy-4-methylphenyl]-1-thio-D-glucitol hydrate), a novel SGLT2 inhibitor in vitro and in vivo. EXPERIMENTAL APPROACHInhibition of glucose uptake by TS-071 was studied in C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 21 publications
5
57
0
Order By: Relevance
“…Accordingly, the results of the meal tolerance tests performed in this study revealed that luseogliflozin improved PPG without excess insulin secretion, which suggests that luseogliflozin might have favorable properties in the treatment of T2DM. Similar results were observed in the prior exploratory phase II study 19 and in several preclinical studies in Zucker fatty rats 16 . Furthermore, luseogliflozin prevented decreases in pancreatic b-cells in streptozotocin-treated rats, an animal model characterized by dysfunctional insulin secretion.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Accordingly, the results of the meal tolerance tests performed in this study revealed that luseogliflozin improved PPG without excess insulin secretion, which suggests that luseogliflozin might have favorable properties in the treatment of T2DM. Similar results were observed in the prior exploratory phase II study 19 and in several preclinical studies in Zucker fatty rats 16 . Furthermore, luseogliflozin prevented decreases in pancreatic b-cells in streptozotocin-treated rats, an animal model characterized by dysfunctional insulin secretion.…”
Section: Discussionsupporting
confidence: 76%
“…Preclinical studies have shown that luseogliflozin is a specific and selective SGLT2 inhibitor 15 and that luseogliflozin improved glucose tolerance and reduced hyperglycemia in animal models of diabetes 16 . In a phase I study of luseogliflozin in healthy individuals 17 and a clinical pharmacology study that assessed the pharmacokinetic and pharmacodynamic profiles of luseogliflozin in patients with T2DM 18 , luseogliflozin dose dependently increased urinary glucose excretion without causing hypoglycemia.…”
Section: Including Luseogliflozin [Ts-071; (1s)-15-anhydro-1-[5-(4mentioning
confidence: 99%
“…Inhibition of SGLT2 promotes urinary glucose excretion by preventing the reuptake of filtered glucose in the proximal tubules of the kidney, consequently lowering plasma glucose levels 9,10 . Because SGLT2 inhibitors have an insulin-independent mechanism of action, these are expected to improve glycemic control with a low risk of major hypoglycemic events 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Because SGLT2 inhibitors have an insulin-independent mechanism of action, these are expected to improve glycemic control with a low risk of major hypoglycemic events 11 . Luseogliflozin -a novel, orally bioavailable, 1-thio-D-glucitol derivative and a highly selective inhibitor of SGLT2 9,12 -lowered glucose levels by promoting urinary glucose excretion in animal models 12 . Results from the previous 12-week exploratory and dose-finding (phases 2a and 2b, respectively) clinical studies have shown that once daily administration of luseogliflozin leads to significant improvements in HbA1c as well as other glycemic parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Luseogliflozin is a novel selective SGLT2 inhibitor 5,6) currently marketed for the treatment of T2DM. The recommended dose is 2.5 mg (or 5 mg depending on the symptoms) once daily before or after breakfast.…”
Section: -4)mentioning
confidence: 99%